EVALUASI INVESTASI PROPERTI PADA PERUMAHAN BUMI KANJURUHAN (STUDI PADA PT. KHARISMA KARANGPLOSO) - Kalis Ayuk Widiastuti (Manajemen Bisnis, 2017)
Business Listing means issuing or investing in land or buildings plus, the benefits in the form of purchasing power protection against inflation and get the added value of its development, such as commercial or residential used. PT. Kharisma Karangploso build Housing Project Earth Kanjuruhan to meet the basic needs of society, especially civil servants to perform simple but decent housing development. This study aimed to determine the Evaluation of Development Project Feasibility Study Earth Kanjuruhan that in value in accordance with aspects of the Feasibility Study and also in accordance with the assessment of investment criteria. The result of this study indicate that the feasibility study of business is considered feasible and the result assesment of investment criteria at PP (Payback Periode) for 4 years 3 month 12 days, ARR (Average ate of Return) amount30,92 % > 6,148 % , the result of  NPV (Net Pesent Value) is positive187.940.169, IRR (Internal Rate of Return) 8,6975 % > 6,148 %, and the last PI (Profitability Index) 1,449> 1.